Kontribusi Semarang-Cheribon Stoomtram (SCS) Maatschappij dalam perkembangan industri gula di Karesidenan Cirebon - Fauzi, Muhammad Nur; Armiyati, Laely; Jayusman, Iyus; Sofiani, Yulia (Estoria: Journal of Social Science and Humanities, 2025)
In the 20th century, Cirebon Residency became a sugar-producing area for the Dutch East Indies Government. This study aims to analyze the development of the sugar industry in the Cirebon Residency in the period 1897-1930, to find out the development of railway companies in the Cirebon Residency in 1897-1930, and to understand the role of SCS in the development of the sugar industry in the Cirebon Residency in 1897-1930. This research uses historical methods that include heuristics, source criticism, interpretation, and historiography. The heuristic stage is carried out through the search of primary and secondary sources. The source is then verified using internal and external criticism. Verified sources are then interpreted and written in historiography. The results of this study show that the increase in the sugar industry in Cirebon Residency began after the Agrarian Law of 1870 which made it easier for private entrepreneurs to invest, including in sugar commodities. The increasing demand for sugar exports has made the Government of the Dutch East Indies strive to improve transportation facilities in Cirebon, one of which is through the construction of railway lines. This project involves several companies including Semarang-Cheribon Stoomtram (SCS). The construction of the railway began to be carried out by the SCS company in 1895. The SCS company succeeded in inaugurating the first railway line in Cirebon inaugurated in 1897, followed by the construction of a tram line in the Cirebon Residency in the period 1901-1930 connecting Prujakan-Kadhipaten. The construction of railway lines and trams by SCS had an impact on the increase in sugar factories in Cirebon Residency so that the sugar industry grew in 1897-1930. This development is shown by the increase in the number of sugar factories in Cirebon which affects the increase in sugar production and exports.